A Review of Data Mining Techniques and Its Applications (International Journal of Innovative Research in Computer Science & Technology, 2021)
Knowledge Discovery in Databases  (KDD) is another name for data mining. It's also known  as the process of extracting interpretable, intriguing and  valuable statistics from unstructured data. There are a  variety of resources which generally produce huge  amounts of raw data. This is the primary cause for the fast  growth of data mining applications. This article discusses  data mining methods and their applications, including  scholastic data mining (SDM), life sciences, commerce,  finance, and medicine among others. We put current  methods together to see how data mining might be used  to various areas. Our classification focuses on research  that was published between 2007 and 2017. We provide a  simple and brief perspective of various models used in  data mining with this classification.
Keywords: EDM; Educational Data Mining; KDD; Knowledge Discovery in Database; LMS; Learning Management System; SNA; Social Network Analysis